Work-family conflict, subjective well-being, burnout, and their effects on presenteeism - Ozduran, Ali; Saydam, Mehmet Bahri; Eluwole, Kayode Kolawole; Mertens, Ememabasi Uwem (Routledge Journals, Taylor & Francis Ltd, 2025)
Work arrangement and flexible work settings are becoming increasingly important in service organizations in an era ravaged by pandemic disruptions. Drawing upon the job demands-resources theory, this study examines the mediating roles of subjective well-being (SWB) and burnout in the relationship between work-family conflict (WFC) and presenteeism. The paper also examined the moderating role of work shifts in the direct relationships between WFC, SWB, burnout, and presenteeism. The data was gathered from 332 workers in Northern Cyprus hotels. The relationships were analyzed by 'structural equation modeling'. Our research found that WFC is positively related to presenteeism. Furthermore, the intervening roles of burnout and SWB on the relationship between WFC and presenteeism were tested, and our data supported the mediated path through SWB. Still, they did not support the mediated path through burnout. Work shifts significantly moderated the positive relationship between burnout and presenteeism. Practical and theoretical implications have been discussed.
Keywords: Subjective well-being; burnout; presenteeism; work shifts; work-family conflict; hospitality employees